2020
DOI: 10.1063/5.0023286
|View full text |Cite
|
Sign up to set email alerts
|

Observation of surface dominated topological transport in strained semimetallic ErPdBi thin films

Abstract: In this Letter, we present experimental observation of surface-dominated transport properties in [110]-oriented strained (∼1.6%) ErPdBi thin films. The resistivity data show typical semi-metallic behavior in the temperature range of 3 K ≤ T ≤ 350 K with a transition from semiconductor- to metal-like behavior below 3 K. The metallic behavior at low temperature disappears entirely in the presence of an external magnetic field >1 T. The weak-antilocalization (WAL) effect is observed in magneto-conductance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Figure 4 d shows the Dingle plots at 1.9 K, 3 K and 4 K, the slope of linear fitting to the data points gives Dingle temperature ~ 5 K. The transport lifetime ( ) and mean free path ( ) of carriers are estimated using the relations, and as ~ 2.43 × 10 –13 s and 78 nm, respectively. The carrier mobility ( ) ~ 3694 is estimated for strained YPdBi thin films, which is quite high among other non-trivial half Heusler alloys like LuPdBi (2100 ) 34 , ErPdBi (1035 ) 14 , DyPdBi (1780 ) 17 and YPtBi(1486 ) 18 . All the parameters extracted from the different fits are listed in the Table 1 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 4 d shows the Dingle plots at 1.9 K, 3 K and 4 K, the slope of linear fitting to the data points gives Dingle temperature ~ 5 K. The transport lifetime ( ) and mean free path ( ) of carriers are estimated using the relations, and as ~ 2.43 × 10 –13 s and 78 nm, respectively. The carrier mobility ( ) ~ 3694 is estimated for strained YPdBi thin films, which is quite high among other non-trivial half Heusler alloys like LuPdBi (2100 ) 34 , ErPdBi (1035 ) 14 , DyPdBi (1780 ) 17 and YPtBi(1486 ) 18 . All the parameters extracted from the different fits are listed in the Table 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Even more interestingly, a recent theoretical studies have indicated the possibility to engineer non-trivial topological states in an otherwise trivial half-Heusler system by strain engineering. While these non-trivial surface states can be detected in ultra-pure samples by angle resolved photoemission spectroscopy and other surface sensitive techniques 10 13 , whereas transport measurements provide a relatively easy way to detect the surface states 6 , 14 18 . This is possible since the surface states are topologically protected and conserve time reversal symmetry which can be broken by an applied external magnetic field providing a pathway to detect them using transport measurements 3 , 6 , 16 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Various band structure parameters are extracted from analysis of SdH oscillations, see Table S2. From these values listed in the ±for samples D0, D2, D5 and DPB respectively using the well-known method of Landau level fan diagram 9,24,36,44 , see Fig. S5.…”
Section: Figurementioning
confidence: 99%
“…Using DFT, Chadov et al predicted that band structure of YPdBi can be tuned between topologically trivial and non-trivial state by varying the lattice constant and/or spin orbit coupling strength of the material system 6 . Although the lattice could be strained by applying uniaxial pressure, an easier way is to grow epitaxial oriented thin films on carefully selected substrates to induce a lattice strain 9,[24][25][26] . We have shown in an earlier work using experimental and band structure computations that ~3.12% strained YPdBi (~30nm) thin films are topologically non-trivial 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation